Extensive DNA Barcoding of Lepidoptera of Crete (Greece) Reveals Significant Taxonomic and Faunistic Gaps and Supports the First Comprehensive Checklist of the Island’s Fauna - Peter Huemer; Kai Berggren; Leif Aarvik; Erwin Rennwald; Axel Hausmann; Andreas Segerer; Giorgia Staffoni; Aina Mærk Aspaas; Apostolos Trichas; Paul D. N. Hebert (Insects)
Comprehensive genetic surveys of Lepidoptera are still largely lacking across most of the eastern Mediterranean. Consequently, there is a lack of modern, taxonomically validated checklists that meet current scientific standards. In this study, we analyze the butterfly and moth fauna of Crete (Greece) for the first time, based on 3110 DNA barcode sequences, primarily obtained from specimens based on our own sampling program. Building on these data, and incorporating previously published records from print sources and online forums, we establish the first comprehensive checklist of the island’s fauna. In total, the occurrence of 1230 species from 62 families is confirmed, with 724 of them genetically verified. Among them, 75 species appear to be island endemics. The checklist includes 125 newly recorded species for Crete, validated by DNA barcoding (with 36 also being new for Greece), along with 23 species confirmed solely through morphological study, and another 16 only documented by photographs. Conversely, 212 previously reported species had to be removed as likely invalid. Furthermore, 112 unidentified sequence clusters (BINs—Barcode Index Numbers) were documented, taxonomic uncertainties that will require future integrative resolution.